Kano approach for developing learning experiences in an educational service industry - Nindiani, Aina; Suhara, Ade; Gusni (International Journal of Psychosocial Rehabilitation, 2020)
This research aimed to identify the learning process and assessment to develop students’ learning experiences using the Kano approach. The objects of this research were students of industrial engineering and civic education programs. The sampling technique implemented was proportionate stratified random sampling by taking samples at all students’ levels of the academic year. By adopting the National Higher Education Standard to build the attributes, the result showed that there were differences in learning experiences between industrial engineering and civic education programs on ten attributes (29,41%). The highest satisfaction coefficient for industrial engineering students was attributed no. 4, The lecturer implements a simulation learning method (0,52), and the highest dissatisfaction coefficient was attributed no. 2, implementation of the learning process in accordance with SLD (-0,62). While For civic education students, the highest satisfaction coefficient was attributed no. 17, the lecturer implements a community engagement form of learning (0,50); the highest dissatisfaction coefficient was attributed no. 2, implementation of the learning process in accordance with SLD (-0,44). Follow-up recommendations were proposed to develop better learning experiences for attributes categorized in must-be, attractive, and one-dimensional to improve satisfaction in the future.